Asymptotic Behavior of Certain Integrodifferential Equations - Said Grace; Elvan Akin (Discrete Dynamics in Nature and Society)
This paper deals with asymptotic behavior of nonoscillatory solutions of certain forced integrodifferential equations of the form: atx′t′=e(t)+∫ct‍(t-s)α-1k(t,s)f(s,x(s))ds,  c>1,  0<α<1. From the obtained results, we derive a technique which can be applied to some related integrodifferential as well as integral equations.